PUBLIC AWARENESS ABOUT THE TRADITION OF UNDER-AGE MARRIAGE TOWARDS CHILDREN`S RIGHTS ACCORDING WITH LAW NO. 23 OF 2002 - Solikhah, Agi (Jurnal Civicus, 2014)
This research try to reveal society awareness about the underage wedding traditions of children's rights in Sampiran village, and how of society understanding the under-age marriage, the factors that influence the level of society awareness about the marriage under the age of children's rights, the role and function of civic education to increase society awareness about underage marriage, and how the efforts made to minimize the occurrence of under-age marriage. This research used a qualitative approach with case study methods and data collection is done through observation, interviews, documentation and literature studies.Keywords: Law Awareness, community, tradition, under-age marriage, and children's rights.